A protocol for a scoping and qualitative study to identify and evaluate indications for damage control surgery and damage control interventions in civilian trauma patients. Issue 7 (7th July 2014) - Roberts, Derek J; Zygun, David A; Kirkpatrick, Andrew W; Ball, Chad G; Faris, Peter D; Bobrovitz, Niklas; Robertson, Helen Lee; Stelfox, H Thomas
Abstract : Introduction: Initial abbreviated surgery with planned reoperation (damage control surgery) is frequently used for major trauma patients to rapidly control haemorrhage while limiting surgical stress. Although damage control surgery may decrease mortality risk among the severely injured, it may also be associated with several complications when inappropriately applied. We seek to scope the literature on trauma damage control surgery, identify its proposed indications, map and clarify their definitions, and examine the content and evidence on which they are based. We also seek to generate a comprehensive list of unique indications to inform an appropriateness rating process. Methods and analysis: We will search 11 electronic bibliographic databases, included article bibliographies and grey literature sources for citations involving civilian trauma patients that proposed one or more indications for damage control surgery or a damage control intervention. Indications will be classified into a predefined conceptual framework and categorised and described using qualitative content analysis. Constant comparative methodology will be used to create, modify and test codes describing principal findings or injuries (eg, bilobar liver injury) and associated decision variables (eg, coagulopathy) that comprise the reported indications. After a unique list of codes have been developed, we will use the organisational system recommended by the RAND/University of California, Los Angeles (RAND-UCLA) Appropriateness Rating Method to group principal findings or injuries into chapters (subdivided by associated decision variables) according to broader clinical findings encountered during surgical practice (eg, major liver injury). Ethics and dissemination: This study will constitute the first step in a multistep research programme aimed at developing appropriate, evidence-informed indications for damage control in civilian trauma patients. With use of an integrated knowledge translation intervention that includes collaboration with surgical practice leaders, this research may allow for development of indications that are more likely to be relevant to and used by surgeons. Ethics approval is not required for this study.